2004
DOI: 10.1115/1.1865196
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Modeling and Dynamic Simulation of the Thoroughbred Equine Forelimb During Stance Phase of the Gallop

Abstract: Because thoroughbred racehorses have a high incidence of forelimb musculoskeletal injuries, a model was desired to screen potential risk factors for injuries. This paper describes the development of a musculoskeletal model of the thoroughbred forelimb and a dynamic simulation of the motion of the distal segments during the stance phase of high-speed (18 m/s) gallop. The musculoskeletal model is comprised of segment, joint, muscle-tendon, and ligament information. The dynamic simulation incorporates a proximal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 32 publications
2
46
3
Order By: Relevance
“…The results showed that the strain in the DDF tendon was larger than that in the SDF tendon, contrary to findings obtained from in vivo strain gauge measurements (Butcher et al, 2009;Riemersma et al, 1996). Other modeling studies have produced results that agree more closely with strain gauge measurements by analyzing the torques developed about the MCP and distal interphalangeal (DIP) joints (Meershoek et al, 2001;Swanstrom et al, 2005a;Wilson et al, 2001) rather than the carpal joint, but these studies have focused only on the portion of the limb below the carpus without considering the important actions of the carpal and digital extensor muscles.…”
Section: Introductioncontrasting
confidence: 55%
See 3 more Smart Citations
“…The results showed that the strain in the DDF tendon was larger than that in the SDF tendon, contrary to findings obtained from in vivo strain gauge measurements (Butcher et al, 2009;Riemersma et al, 1996). Other modeling studies have produced results that agree more closely with strain gauge measurements by analyzing the torques developed about the MCP and distal interphalangeal (DIP) joints (Meershoek et al, 2001;Swanstrom et al, 2005a;Wilson et al, 2001) rather than the carpal joint, but these studies have focused only on the portion of the limb below the carpus without considering the important actions of the carpal and digital extensor muscles.…”
Section: Introductioncontrasting
confidence: 55%
“…The ligaments were represented as passive elastic structures. The force-length curve of each tendon and ligament was modeled by fitting a third-order polynomial function to experimental data reported in the literature (Jansen et al, 1993a;Jansen et al, 1998;Kostyuk et al, 2004;Lochner et al, 1980;Meershoek et al, 2001;Swanstrom et al, 2004;Swanstrom et al, 2005a;Swanstrom et al, 2005b;Weller, 2006). The lengths, moment arms and tendon wrapping directions of each muscle and ligament were calculated using a software program called OpenSim (Delp et al, 2007).…”
Section: Musculoskeletal Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…In this model, a slow gallop was defined as a velocity of 10m/s at 2.8 times walking force with a peak vertical force of 1.8 times body weight. A fast gallop was defined as a velocity of 17m/s (Swanstrom et al, 2005) at 3.5 times walking force with a peak vertical force of 2.3 times body weight. All contact and muscle forces were assumed to be proportional to walking forces, and were based on muscle MVC and equine EMG data for walking.…”
Section: Creation Of Equilibrium Modelmentioning
confidence: 99%